2011
DOI: 10.2460/ajvr.72.7.905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body position, imaging plane, and observer on computed tomographic measurements of the lumbosacral intervertebral foraminal area in dogs

Abstract: Repeated measurements of the LSIF area in images obtained during LSJ extension may be unreliable as a result of interobserver variability and the effects of dog positioning and CT slice orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 33 publications
6
29
0
Order By: Relevance
“…In the present study, significant differences in intervertebral foraminal area were found between parasagittal and parasagittal oblique planar measurement methods. Previous studies also found differences between parasagittal and parasagittal oblique methods for quantifying intervertebral foraminal areas at L7‐S1 using CT and MRI . In both of these studies, the parasagittal planar method for measuring intervertebral foraminal area yielded values that were significantly larger than the parasagittal oblique measurement techniques.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In the present study, significant differences in intervertebral foraminal area were found between parasagittal and parasagittal oblique planar measurement methods. Previous studies also found differences between parasagittal and parasagittal oblique methods for quantifying intervertebral foraminal areas at L7‐S1 using CT and MRI . In both of these studies, the parasagittal planar method for measuring intervertebral foraminal area yielded values that were significantly larger than the parasagittal oblique measurement techniques.…”
Section: Discussionmentioning
confidence: 81%
“…Results from the current study also indicated that lumbosacral angle measurement techniques should be standardized in future research studies evaluating effects of exercise prescriptions on lumbosacral range of motion values. Significant differences were found between CT lumbosacral angles measured using techniques 1 and 2 for both flexion and extension hip positions. In addition, lumbosacral range of motion values also differed by measurement technique.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations